2016
DOI: 10.1097/prs.0000000000002032
|View full text |Cite
|
Sign up to set email alerts
|

Applying to Integrated Plastic Surgery Residency Programs: Trends in the Past 5 Years of the Match

Abstract: Within the setting of increased applicant competitiveness, the authors recommend maximizing subjective qualities in order to differentiate themselves from a highly eligible applicant pool. In addition, applicants should diversify the types of programs at which they interview to maximize their chances of matching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
54
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(56 citation statements)
references
References 17 publications
0
54
0
Order By: Relevance
“…With a strong emphasis on research, there is a new rise in the number of students taking time off from medical school to pursue dedicated research fellowships. 1 , 3 Mehta et al 1 recently reported that, on average, research fellows publish 5.25 articles and give 5.4 oral presentations and 3 poster presentations per year, exceeding the productivity expectations of polled faculty. Most importantly, the match rate from 2013 to 2016 for those who completed a research fellowship was significantly higher than that for those who did not (97% versus 81%).…”
Section: Objective Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…With a strong emphasis on research, there is a new rise in the number of students taking time off from medical school to pursue dedicated research fellowships. 1 , 3 Mehta et al 1 recently reported that, on average, research fellows publish 5.25 articles and give 5.4 oral presentations and 3 poster presentations per year, exceeding the productivity expectations of polled faculty. Most importantly, the match rate from 2013 to 2016 for those who completed a research fellowship was significantly higher than that for those who did not (97% versus 81%).…”
Section: Objective Factorsmentioning
confidence: 99%
“…The most important and commonly cited objective criteria considered in selection of plastic surgery applicants are research productivity, USMLE scores, AOA membership, and medical school reputation. 1 , 3 , 5 8 …”
Section: Objective Factorsmentioning
confidence: 99%
See 3 more Smart Citations